Air entrained into viscous liquid by a disk: Confinement induced suppression of breakup - Hana Nakazato; Ko Okumura (Physical Review Research, 2022)
When a solid object falls into a bath of viscous liquid due to gravity with zero initial velocity, air can be entrained into the viscous liquid with the solid. We study such an air entrainment by a metal disk falling in the direction perpendicular to its axis in a confined space. We previously reported that the entrained air is extended and forms a thin sheet, which finally detaches from the disk with a topological change: The extended air breaks up into two parts, after which the lower part becomes a small bubble and the upper part starts retracting upwards [Phys. Rev. Fluids 3, 054004 (2018)2469-990X10.1103/PhysRevFluids.3.054004]. In the present paper, we further confined the air sheet using thinner disks, to surprisingly find a complete suppression of a topological change: The entrained air detaches from the disk without breakup (i.e., without creating a small bubble) but with forming, instead of a sheet, an elliptic corn at the tip. The physical origin of the confinement induced suppression of breakup is discussed from the viewpoints of the inversion of curvature of an air-liquid interface and the movement of the contact line. Near the corn-forming detachment, three length scales characterizing the dynamics are all proportional to a single characteristic length as in the previous sheet-forming case, which leads to a fixed aspect ratio for the elliptic corn in the present case. The characteristic scale satisfies a simple scaling law, which is different from the previous sheet-forming case, and governs the self-similar dynamics near the detachment point. The present corn-forming case provides a remarkable scenario for the self-similar dynamics discussed in various fields such as statistical physics, applied mathematics, and hydrodynamic topology transitions.